PENGARUH KECEMASAN KOMUNIKASI TERHADAP INTENSITAS KOMUNIKASI INTERPERSONAL DENGAN TEMAN SEBAYA (PEER GROUP) MELALUI KEPERCAYAAN DIRI BERKOMUNIKASI PADA SISWA TULI DI YAYASAN SETARA SEMARANG - Desi Sulistianingsih; wiwid Noor Rakhmad (Interaksi Online, 2026)
The high levels of interpersonal communication barriers experienced by Deaf students in their interactions with peers is the background for this study. Deaf students frequently encounter communication anxiety triggered by fears of rejection and miscommunication, which in turn undermines their communication self-confidence and potentially reduces the intensity of their interpersonal communication. This study aims to examine the effect of communication anxiety on the intensity of interpersonal communication through the mediation of communication self-confidence among Deaf students at Yayasan Setara Semarang. To address the research objectives, this study employed the Anxiety/Uncertainty Management (AUM) theory and Cognitive Dissonance Theory within a quantitative explanatory research design. The sampling technique used was total sampling, involving 35 respondents. Data were analyzed using Structural Equation Modeling-Partial Least Squares (SEM-PLS) with the assistance of SmartPLS 4 software. This analytical method was selected due to its suitability for testing mediation models and its effectiveness with relatively small sample sizes. The results indicate that communication anxiety has a significant negative effect on the intensity of interpersonal communication among Deaf students. Higher levels of communication anxiety are associated with lower intensity of interpersonal interactions with peers. Furthermore, the findings reveal that communication anxiety influences interpersonal communication intensity indirectly through communication self-confidence as a mediating variable. Based on these findings, it is recommended that educators and the social environment develop communication programs focusing on anxiety management and the enhancement of students’ communication self-confidence to foster more inclusive and supportive social interactions.